Ensemble methods : foundations and algorithms - Zhou, Zhi-Hua, Ph. D. (Boca Raton, FL : Taylor & Francis, 2012)
"This comprehensive book presents an in-depth and systematic introduction to ensemble methods for researchers in machine learning, data mining, and related areas. It helps readers solve modem problems in machine learning using these methods. The author covers the spectrum of research in ensemble methods, including such famous methods as boosting, bagging, and rainforest, along with current directions and methods not sufficiently addressed in other books. Chapters explore cutting-edge topics, such as semi-supervised ensembles, cluster ensembles, and comprehensibility, as well as successful applications"--
Includes bibliographical references (p. 187-218) and index.
Keywords: Multiple comparisons (Statistics); Set theory; Mathematical analysis; BUSINESS & ECONOMICS / Statistics; COMPUTERS / Database Management / Data Mining; COMPUTERS / Machine Theory